Korean peace building and Sino–US relations: an "Ad-hoc" concert of interests?. Issue 1 (2nd January 2019) - Kurata, Hideya
ABSTRACT: The Korean Peninsula is perceived by both the United States (US) and China as the region where they could cooperate despite other disputed problems. The Four-Party Talks were proposed amid a crisis in the Taiwan Strait in 1996, and the Six-Party Talks were convened during the controversies over the subsequent Iraq War in early 2000s. The author argues whether this " Ad-hoc Concert" still survives as an analytic framework for examining Sino–US relations on the Korean Peninsula, notwithstanding the new dimension of collective security as a result of Democratic People's Republic of Korea (DPRK, North Korea)'s nuclear issues with respect to the United Nation Security Council (UNSC). This paper first examines the Chinese initiatives in the nuclear crisis in 2016–17; it makes an assessment of the developments of the triangulated US–China–DPRK relationship after Chairman Kim Jongun referred to the "denuclearization of the Korean Peninsula" in early 2018. In the successive Summit meetings that Kim Jongun held with the Republic of Korea (ROK, South Korea)'s President Moon Jaein, and US President Donald Trump, the declaration to end the Korean War dominated those in the triangulated relations. This paper also reviews the controversies related to that declaration and their implication for Sino–US relations. Those implications will provide the basis for an analysis of Sino–US relations on the Korean Peninsula following a speech delivered by US Vice-President Mike Pence in October 2018 that was widely seen as a declaration of a "new cold war" between the US and China.